Studying the relationship of immersion duration and characteristics of natural materials FAD to fish aggregation in the sea - Arham Rumpa; Najamuddin Najamuddin; Safruddin Safruddin; Muhammad Abduh Ibnu Hajar (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rumpa A, Najamuddin, Safruddin, Hajar MAI. 2022. Studying the relationship of immersion duration and characteristics of natural materials FAD to fish aggregation in the sea. Biodiversitas 23: 5481-5490. An understanding of immersion duration and the characteristics of natural materials Fish Aggregating Devices (FAD) on fish aggregation in the sea is crucial in developing more effective fishing strategies in FAD areas. The aim of the study was to understand the relationship between immersion duration and characteristics of FADs made from natural materials on the schooling aggregation of mackerel scad (Decapterus russelli) in the sea. The research was conducted from April 2021 to March 2022 in Bone Bay, Indonesia. The type of research was experimental fishing 78 times down at sea to observe the relationship between FAD construction and fish schools. The results demonstrated that the growth of invertebrates in the construction component of FADs based on the period of immersion in the sea at the immersion period of >30 days showed a high growth rate of algae, hydrozoa and crustacean species at the bottom of the raft. The endurance of the coconut leaves attractor at a duration of 3-4 weeks was the best condition for immersion duration in the sea because schooling fish were more concentrated around the attractor at an average distance of 1.2 m, while at a duration of 5-6 weeks the attractor had damaged and the fish schooling was less concentrated. Based on the arrival of schooling fish in FAD areas, the fastest average duration was 3-4 weeks, namely in transitional season 1. The presence of crustacean species caused fish schooling only to be concentrated at a distance of 2-3 m at the time of fishing. In the fishing strategy, the treatment of FADs using dried coconut leaves attractors showed more concentrated fish schooling and calmer fish movement pattern compared to the use of fresh coconut leaves attractor. The characteristics of the components making up FADs had a direct impact on the effectiveness of attracting and concentrating fish. In addition, the characteristics also influenced the schooling distance of fish at the center point of the FAD raft before the fishing gear was lowered.